2015
DOI: 10.1039/c4lc01038h
|View full text |Cite
|
Sign up to set email alerts
|

Real-time tracking, retrieval and gene expression analysis of migrating human T cells

Abstract: Dynamical analysis of single-cells allows assessment of the extent and role of cell-to-cell variability, however traditional dish-and-pipette techniques have hindered single-cell analysis in quantitative biology. We developed an automated microfluidic cell culture system that generates stable diffusion-based chemokine gradients, where cells can be placed in predetermined positions, monitored via single-cell time-lapse microscopy, and subsequently be retrieved based on their migration speed and directionality f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 26 publications
(29 reference statements)
3
39
0
2
Order By: Relevance
“…Taken together, we reconfirm previous reports of the capability to generate highly controllable diffusion-based chemokine gradients in microfluidic devices1415. We then integrated the controlled immobilization of chemokines in this microfluidic device.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Taken together, we reconfirm previous reports of the capability to generate highly controllable diffusion-based chemokine gradients in microfluidic devices1415. We then integrated the controlled immobilization of chemokines in this microfluidic device.…”
Section: Resultssupporting
confidence: 86%
“…We have previously shown that chemotaxis can be induced in T cells by exposure to a soluble gradient of the chemokine CXCL12 generated in a microfluidic migration device14. To recapitulate this finding for other immune cells, we exposed DCs to a continuously rising gradient of CCL19 or control conditions in migration chambers of our microfluidic device (Fig.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…It is shown that the methods implementing continuous cell tracking have a promising potential to overcome the complexity of investigation of tissue growth and hemostasis at the cellular level [222]. Analysis of cell tracking within microfluidic devices which provide a real time monitoring of biological samples in a controllable condition is a desirable achievement that can reveal the extensive unknown factors in tissue development studies [223,224]. However, these techniques are not applicable without implementing computational and statistical analyses to process large data obtained from monitoring the samples [225].…”
Section: Methodsmentioning
confidence: 99%
“…Two examples are studies that correlated cell motility with proteomic 90 or transcriptome analysis 32 . A third example was an analysis of how specific cancer cells respond to targeted inhibitors as the physical environment is altered from normoxia to hypoxia 31 .…”
Section: Applications Of Single Cell Analysis: Uncovering New Biologymentioning
confidence: 99%